2009
DOI: 10.1186/1748-717x-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and job satisfaction of physicians, radiographers, nurses and physicists working in radiotherapy: a multicenter analysis by the DEGRO Quality of Life Work Group

Abstract: Background: Ongoing changes in cancer care cause an increase in the complexity of cases which is characterized by modern treatment techniques and a higher demand for patient information about the underlying disease and therapeutic options. At the same time, the restructuring of health services and reduced funding have led to the downsizing of hospital care services. These trends strongly influence the workplace environment and are a potential source of stress and burnout among professionals working in radiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
74
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 30 publications
13
74
1
7
Order By: Relevance
“…[7] The doctors who had more night shifts were found to be more dissatisÞ ed with their job, which was also found by Sehlen among physicians in Germany. [8] Majority (88%) of the doctors perceived their work environment as good/average, which is similar to the results found by Madaan, who found that majority (76.7%) of the residents in a tertiary hospital in Delhi perceived their environment at work as being 'cordial.' [5] In the present study, salary was considered good by only 14.8% of the doctors, while Madaan found that about 27% of the doctors (faculty in addition to the residents) said that their salary was proportional to the workload.…”
Section: Discussionsupporting
confidence: 78%
“…[7] The doctors who had more night shifts were found to be more dissatisÞ ed with their job, which was also found by Sehlen among physicians in Germany. [8] Majority (88%) of the doctors perceived their work environment as good/average, which is similar to the results found by Madaan, who found that majority (76.7%) of the residents in a tertiary hospital in Delhi perceived their environment at work as being 'cordial.' [5] In the present study, salary was considered good by only 14.8% of the doctors, while Madaan found that about 27% of the doctors (faculty in addition to the residents) said that their salary was proportional to the workload.…”
Section: Discussionsupporting
confidence: 78%
“…With high technology costs and an increased complexity of the equipment, the technology is sometimes changing faster than current training programs can be provided. At the same time, increased requirements (health services restructuring, increasing consumer orientation, increased regulations and demand for continuous quality improvement and learning) result in an increased individual workload for the staff of radiology departments (3,4,6).…”
Section: Discussionmentioning
confidence: 99%
“…Hospital administrators rely on radiology to increase the revenue through higher patient volume, which in turn requires greater efficiency and productivity from the radiographers. This rising demand for radiological services may put immense pressure on the employees and influences the workplace environment and staff morale [3][4][5][6].…”
Section: [[Please Note Use Of Square Brackets For Reference Citationsmentioning
confidence: 99%
“…Este concepto abarca la realidad en la que la creciente burocracia administrativa, unida a factores sociales, tecnológicos y económicos, aumenta la exigencia en el rendimiento de los profesionales. En consecuencia, su CVP (13) pasa a un segundo plano, lo que contribuye al incremento en los niveles de estrés laboral, ya considerados elevados en los profesionales de la salud (14)(15)(16)(17). Esta circunstancia puede conducir al padecimiento del ampliamente descrito…”
unclassified